Stem Cell from Human Exfoliated Deciduous Teeth (SHED) versus Human Umbilical Cord Blood Mononuclear Cells (cbMNC) Transplantation in Neural Damage Reduction in Rat Model of Cerebral Ischemia - ramli, yetty (Stem Cell Research and Development Center, Universitas Airlangga, 2018)
Ischemic stroke is one of major cause of mortality and disability in Indonesia. Stem Cells are considered as a promising therapy for ischemic stroke. In this study, we compared therapeutic potency of Stem cell from human exfoliated deciduous teeth (SHED) and Human umbilical cord blood mononuclear cell (cbMNC) using rat models of ischemic stroke. Following middle cerebral artery occlusion (MCAO), twenty male wistar rats were divided into four groups : normal rats (n=5), rats undergone permanent MCAO (n=5) as the control (stroke) group, rats undergone permanent MCAO and SHED transplantation (n=5) and rats undergone permanent MCAO and cbMNC transplantation (n=5) as the treatment group. SHED transplantation was performed at the acute phase after MCAO by intravenous injection. Histopathological evaluation of the neuron death ratio with hematoxylin and eosin staining confirmed that there was no significant differences at comparative study of neuron death ratio in rats transplanted with SHED and rats transplanted with cbMNC (p=0,81). SHED and cbMNC transplantation at acute stroke showed reduction in the neuron death ratio in the brain of rat models with ischemic stroke, and may provide an opportunity for neuroprotection and neural regeneration after ischemic stroke.